One or Multiple Complicated Grief(s)? The Role of Kinship on Grief Reactions. (September 2017) - Fernández-Alcántara, Manuel; Zech, Emmanuelle
Previous research has paid little attention to the role of kinship in understanding the specific profiles of complicated grief (CG) reactions. To address this underinvestigated topic, the Inventory of Complicated Grief was used in five groups of bereaved participants ( N = 1, 105) that differed in their family relationship with the deceased (child, spouse/romantic partner, sibling, parent, and grandparent). Results identified kinship relationship as the variable that predicted the highest amount of variance in the intensity of CG (standardized β = –.55), above other predictors such as gender, time since loss, or circumstances of death. More important, distinct profiles of CG reactions were found depending on kinship. These results highlight kinship as a major predictor of CG and open a new line of research that serves to clarify the role of kinship along with other risk factors.